Making immigrant rights real : nonprofits and the politics of integration in San Francisco - De Graauw, Els (Cornell University Press, 2016)
More than half of the 41 million foreign-born individuals in the United States today are non-citizens, half have difficulty with English, a quarter are undocumented, and many are poor. As a result, most immigrants have few opportunities to make their voices heard in the political process. Nonprofits in many cities have stepped into this gap to promote the integration of disadvantaged immigrants. They have done so despite notable constraints on their political activities, including limits on their lobbying and partisan electioneering, limited organizational resources, and dependence on government funding. This book examines how immigrant-serving nonprofits can make impressive policy gains despite these limitations.